Faktor Kemudahan Pengguna, Manfaat, dan Risiko Terhadap Minat Penggunaan E-Wallet Dana Dalam Pembayaran Non-Tunai Dengan Keamanan Privasi Sebagai Variabel Intervening di Kota Semarang (International Forum of Researchers and Lecturers, 2024)
Science and technology continue to develop in a more sophisticated direction. One of the technological advances in the era of globalization is marked by the Dana e-wallet. The Dana e-wallet is one of the popular alternative digital payment transactions in Indonesia because of its ease of use, benefits, risks and privacy security. The impact offered in terms of user convenience, benefits, risks and privacy security makes people interested in using this e-wallet. The aim of this research is to determine the influence of user convenience, benefits and risks on interest in using the Dana e-wallet with privacy security as an intervening variable. This research uses a causality research design with a quantitative approach and a sampling technique using Non-Probability Sampling. The population in this research is the people in Semarang City. The number of samples taken was 100 respondents. The data analysis methods used are regression analysis, path analysis, and Sobel test. The data obtained in this research was then processed using the IBM SPSS Statistics 23 program.